The effect of Eurycoma Longifolia Jack extract (Tongkat Ali) on serum leptin levels in male rats - Faisal, Ghasak Ghazi; Mustafa Al-Ahmad, Basma Ezzat; Mustafa, Nazih Shaban; Najmuldeen, Ghazi Faisal; Althunibat, Osama Yousef (World Academy of Science, Engineering and Technology (W A S E T), 2013)
Eurycoma Iongifolia Jack (E. L), which is known as Tongkat Ali is a plant which grows up to10 meters high and is found in primary and secondary evergreen and mixed deciduous forests in Burma, China, Thailand, Malaysia, Sumatra, Borneo and the Philippines.It has become famous as a sexual enhancer since it has been proved by various studies to increase the serum testosterone levels in male rats and humans. Recently it has also been shown to increase muscle mass in rats .That made us interested to find out if there is any change in the body fat content which is reflected through the serum leptin concentration. Leptin is a 16 kDa protein hormone that plays a key role in regulating energy intake and energy expenditure, including appetite and metabolism. It is one of the most important adipose derived hormones.The Ob (Lep) gene is located on chromosome 7 in humans. It is manufactured primarily in the adipocytes of white adipose tissue, and the level of circulating leptin is directly proportional to the total amount of fat in the body. Objectives: To study the effect of Eurycoma Longifolia jack (E. L.) extract on the serum leptin level of male rats. Methodology: Mature male Albino Wistar rats where used in this study, we measured the rats’ serum leptin and testosterone level before receiving treatment (control), the rats were divided into two groups ,group A received 5mg/kg body weight twice daily of pure 100:1 concentration E.L. extract, group B received 10mg/kg body weight twice daily of the same extract . The duration of treatment was 6 weeks for both groups. At the end of the experiment, we analyzed the serum leptin and testosterone levels in both groups. Results: The mean serum leptin and testosterone levels for the control group were 1.13ng/ml, 0.79ng/L, group A 1.08ng/ml, 0.98ng/L group B 0.89ng/ml,1.75ng/L respectively. Statistical analysis showed that serum leptin level of group B was significantly lower than that of control group (p<0.001) and group A(p<0.05). On the other hand, no significant difference in serum leptin levels were observed between the control group and group A. The serum testosterone level was significantly higher in group B than control and group A. Conclusion: According to our results we can see that E.L. extract can significantly decrease serum leptin levels however,the effect is dose dependant and maybe affected by the significant rise in serum testosterone level that occurs in group B only. This conclusion is based on previous studies that have reported the existence of a negative correlation between serum testosterone and leptin concentrations.